ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT UNTUK MENABUNG DI BPR SARI BUMI (Studi Kasus Pada BPR Sari Bumi Boyolali Cabang Juwangi) (Students' Journal of Economic and Management, 2014)
Background of this research was the increasing of the people intention to save deposit at the banks in the District Juwangi Boyolali Residence. One of the bank that has the fastest deposit increation is Bank of Common Credit Sari Bumi Branch District Juwangi. With the fact that people intention grown because of the determination inside and because the influence from the surrounding behavior. The researcher intend to study the factors of the people intention to save deposit at the BPR Sari Bumi. This research was quantitative methodes, with the multiple regression analyzis. The research variables consist of intention to save deposit as the dependent variable and internal factors and external factors as the independent variables. The result showed that simultaneously, internal and external factors has influence to the people intention to save deposit positively and significanly with 70,8% influence. Partially, internal and external factors proved influencing the people intention to save deposit. It is proved by the t coefficients 2,797 of the internal factors and 12,308 of the exteral factors that bigger than the t table of 1,646. Keywords : saving intention, internal factors, external factors